Assessment of the Genotoxic Potential of 17β-estradiol in Different Filters Using the Comet Assay (International Journal of Geoscience, Engineering and Technology, 2025)
This study assessed the genotoxicity  of different filtering materials in remediating the hormone 17β-estradiol (E2), an emerging contaminant with genotoxic potential. The comet assay was performed using Allium cepa root cells to evaluate DNA damage after filtration. Filters containing banana biomass, Pleurotus ostreatus biomass, δ-FeOOH, and a combination of the three were tested. All treatments were efficient in reducing E2-induced DNA damage, with δ-FeOOH showing the highest remediation performance, presenting the lowest DNA Damage Index and Damage Frequency. The ImageJ software was used for the analysis of images obtained by epifluorescence microscopy, being essential for accurate measurement of DNA migration. The findings highlight the potential of natural, low-cost materials in the treatment of estrogen-contaminated effluents, supporting the development of sustainable environmental technologies.
Keywords: 17β-estradiol; Genotoxicity; Allium cepa; Biomass; Comet assay